Motor and non-motor wearing-off and its impact in the quality of life of patients with Parkinson's disease - Rodríguez-Violante, Mayela; Ospina-García, Natalia; Dávila-Avila, Ned Merari; Cruz-Fino, Diego; Cruz-Landero, Alejandra de la; Cervantes-Arriaga, Amin (Arquivos de neuro-psiquiatria, 2018)
ABSTRACT The wearing-off phenomenon is common in patients with Parkinson's disease. Motor and non-motor symptoms can fluctuate in relation to the “on/off” periods. Objective: To assess the impact of motor and non-motor wearing-off on activities of daily living and quality of life of patients with PD. Methods: A cross-sectional study was carried out. All patients were evaluated using the Movement Disorders Society Unified Parkinson's Disease Rating Scale. Wearing-off was assessed using the Wearing-Off Questionnaire-19, and quality of life was assessed using the Parkinson's Disease Questionnaire-8. Results: A total of 271 patients were included; 73.4% had wearing-off; 46.8% had both motor and non-motor fluctuations. Patients with both motor and non-motor wearing-off had a worst quality of life compared with those with only motor fluctuations (p = 0.047). Conclusions: Motor and non-motor fluctuations have an impact on activities of daily living and quality of life. Non-motor wearing-off may have a higher impact.